2008
DOI: 10.1196/annals.1429.026
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Development and Menarche

Abstract: Puberty is the developmental process that culminates in reproductive capability and is the result of a complex series of molecular and physiological events. The release of gonadotropin‐releasing hormone from specialized neurons of the hypothalamus begins the hormonal cascade that causes gonadal activation and the physical changes of puberty. Several factors have been proposed to influence the activation of the hypothalamus to trigger puberty, but the involved pathways have not been fully elucidated. The recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 109 publications
1
58
0
2
Order By: Relevance
“…Markers of puberty, including breast and pubic hair development, often begin several years before first menses. 18 Age at menarche started to decline in the early 1900s but has remained fairly constant at 12 to 13 years for the past 60 years. 19 Over the past generation, there has been a dramatic decline in the age at onset of breast development.…”
mentioning
confidence: 99%
“…Markers of puberty, including breast and pubic hair development, often begin several years before first menses. 18 Age at menarche started to decline in the early 1900s but has remained fairly constant at 12 to 13 years for the past 60 years. 19 Over the past generation, there has been a dramatic decline in the age at onset of breast development.…”
mentioning
confidence: 99%
“…1 The timing of menarche has been reported to influence cardiovascular and metabolic health in adolescence and young adulthood, [2][3][4] but its long-term impact on vascular health in middle-age is unclear. Several studies have suggested that early menarche is associated with increased risk of coronary heart disease [5][6][7][8][9][10][11] or stroke, 7 but findings have been inconsistent.…”
mentioning
confidence: 99%
“…is one of the growth factors which may regulate the timing of puberty and puberty regression by inducing the gonadotropin-releasing hormone (GnRH) pulse, gonadotropin, and sex hormone [43]. It is showed that IGF-I increased the expression of gonadotropin-releasing hormone in vitro [43][44][45].…”
Section: Vitamin D and Puberty (The Potential Role Of Vitamin D In Hymentioning
confidence: 99%